Solusi Konflik Sosial dalam Perspektif al-Qurâan - ng, Sukri (Institut Agama Islam Negeri (IAIN) Salatiga, 2016)
Social life, if scrutiny is the main component of interaction between the members.Â In connection with the interaction among members was found various types. TheÂ types of social interaction in general include: cooperative (co-operation), competitionÂ (competition) and conflict (contention). In everyday social life seems besidesÂ characterized by cooperation, constantly marred by various forms of competitionÂ and conflict. Even in social life has never been found all citizens of all time cooperative.Â The teachings of Islam (al-Qurâan) has been tested in the history of the Prophet inÂ unifying the Aus and Kasraj, warring for hundreds of years. Conflict and human,Â these two are inseparable. Therefore, conflict is a part of a necessity in life (minÂ lawazim al-hayat) human. It is not excessive if some experts say that human historyÂ is a history of conflict. But that does not mean that the conflict left without anyÂ attempt to manage and mute. So this paper attempts to explore the spirit to manageand reduce conflicts and solutions in the perspective of the Koran.